Thymolipoma simulating cardiomegaly: a clinicopathological rarity. Issue 1 (February 1977) - Almog, C; Weissberg, D; Herczeg, E; Pajewski, M
Abstract : This report describes a 19-year-old girl with a chest radiograph strongly suggestive of cardiomegaly. Although she did not consent to haemodynamic studies, cardiomegaly wasru led out on the basis of the clinical course. Careful radiological study proved the existence of a large mass in the anterior mediastinum, simulating cardiomegaly. At thoracotomy a thymolipoma weighing 450 g was resected. The pathogenesis of thymolipoma is discussed.